FANATISME PADA PERGURUAN CABANG OLAHRAGA KARATE DITINJAU DARI SOSIAL, BUDAYA DAN OLAHRAGA (STUDI KASUS PADA DOJO DI KABUPATEN JEPARA) (Indonesian Journal for Physical Education and Sport, 2020)
ABSTRACTIta Setiyawati. 2020. Fanaticism in the Karate Sports College in terms of Social, Culture, and Sports (Case Study of the Dojo in Jepara Regency). Thesis, Department of Physical Education, Health, and Recreation, Faculty of Sport Science, Universitas Negeri Semarang. Supervisor: Dr. Heny Setyawati, M.Si. Kata kunci: Fanaticism, Karate, Social, Culture, Sports. This research is motivated by the development of existing colleges in Jepara Regency resulting in increased competition between universities and fanatsime between universities is increasingly visible when in a match. Then there are five karate schools with one school, shotokan. Some universities in Jepara Regency include; Lemkari, Inkai, Inkanas, BKC, and Inkado. The problem in this research is how much the level of fanaticism in the karate sport branch (case study in Dojo in Jepara Regency) in terms of social, cultural and sports. The purpose of this research is to find out how much the level of fanaticism in karate sports is viewed from Culture, Social and Sports (Case Study of Dojo in Jepara Regency) "..Quantitative descriptive research using survey methods. The variable of this study is the level of fanaticism in the karate sports branch of the school by using a population of karate college students in Jepara Regency. A sample of 52 karateka college using accidental sampling technique. Data collection uses observation, documentation and questionnaire / questionnaire. With instruments in the form of a questionnaire / questionnaire. Descriptive percentage of statistical data analysis as a data analysis technique.The results of this study indicate that the level of fanaticism in the karate sport branch in Jepara in terms of social has a category value of 75%. This shows that the level of fanaticism in the karate sport branch in Jepara in terms of social is included in the very high category. The level of fanaticism in the karate sports college in Jepara Regency is seen from the culture of 55.8% which is in the medium category. Then the level of fanaticism in karate sports in the Jepara Regency in terms of sports is 40.4% which is also included in the high category.Based on the results of the study, it can be concluded that fanaticism in the karate sports university based on social review (case study of the dojo in Jepara Regency) shows that it is in the very high category, for cultural review is in the medium category and for sports review is in the high category. Researchers have suggestions that parents and the community can support the development of karate in order to provide the best.